Short communication: The dissimilarity in plant species composition of savanna ecosystem along the elevation gradient on Flores Island, East Nusa Tenggara, Indonesia - Sutomo Sutomo; I Dewa Putu Darma; Rajif Iryadi (Society for Indonesian Biodiversity, 2020)
Abstract. Sutomo, Darma IDP, Iryadi R. 2020. Short communication: The dissimilarity in plant species composition of savanna ecosystem along the elevation gradient on Flores Island, East Nusa Tenggara, Indonesia. Biodiversitas 21: 492-496. Savannas in Indonesia are located from west to the east across the archipelago. The objective of this research was to investigate the dissimilarity of floristic composition among savannas at different elevations in Flores. Sixteen sampling plots, each measuring 20 x 20 m were spread over the lowland, midland, and upland savannas. We analyzed the differences in plant community composition among the savannas using NMDS ordination and SIMPER analyses available in PRIMER V.6. As many as 41 species of plants were found in all of the sampling plots. The lowland savanna plant community consisted of Themeda arguens, Zoesya sp., Chromolaena odorata, Crotalaria sp., Adenanthera pavonina, Ocimum sp., Lantana camara in the groundcover layer, and Ziziphus jujube, and Borassus flabellifer at the tree layer. The midland savanna had almost similar composition, except the occurrence of Imperata cylindrica and Leucaena leucocephala, and the upland savanna plant species were Cyperus sp., Polygala paniculata, I. cylindrica, Melastoma malabathricum, C. odorata, Centella asiatica, Vaccinium sp., and Cymbopogon sp. The savannas in Flores were invaded by invasive exotic species, namely L. camara and C. Odorata which may pose serious threat to the existence of savannas.